Retrato falado : educação estética na construção da identidade social e cultural do aluno - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
This master's thesis is a case study whose purpose is to investigate and think about the role of aesthetic education in the formation of socio-cultural identity of the student, by observing their interactions with art. By the way, this interdisciplinary study is theoretically grounded in conceptions of Lévy (1996), Santaella (2010), Ferraz and Fusari (2009), Vygotsky (2009), Soares (2011), Rojo (2012), Giddens (1991) , Assisi and Rodrigues (2010), Hauser (1995), Benjamin (1992), besides other authors who move between the areas concerned. Te objects of his work are the reference documents of the school (PPP, 2013 and PCN, 1997) and the productions of the research subjects, students of a public school in Goiânia. As diagnostic instruments for data collection we used questionnaires, which were applied to the kids. We’ve also performed aesthetic appreciation workshops, throughout the year 2014, with the pedagogical purpose of enabling students to recognize aesthetic values from the artistic culture in its contemporary context permeated by multicultural productions. Based on the achieved results and analysis of the material produced, we could infer that the aesthetic education is an essential factor for the construction of cultural and social identity of the students. Whith this aesthetic education they can express their inner world through their personal poetic view, to understand it better, in the context of their relationship with the artwork and their pairs.
Keywords: Educação estética; Identidade sociocultural; Cibercultura; Aesthetic education; Socio and cultural; Ciberculture; CIENCIAS HUMANAS::EDUCACAO